Prevalence of Gestational Diabetes Mellitus among Women with Lower Risk for Gestational Diabetes in Siriraj Hospital - Sirirat S. (2023)
Objectives: To determine prevalence of gestational diabetes (GDM) among Thai pregnant women who were at lower risk for GDM and determine possible associated factors. Materials and Methods: A total of 292 pregnant women who had lower risk for GDM who started antenatal care before 20 weeks of gestation were included. All women received GDM screening and diagnosis with 50-g glucose challenge test and 100-g oral glucose tolerance test. Data were extracted from medical record, including baseline characteristics, obstetric data, GDM screening and diagnosis, and pregnancy outcomes. Prevalence of GDM was estimated. Various characteristics and pregnancy outcomes were compared between women with and without GDM. Logistic regression analysis was performed to determine independent risk factors associated with GDM adjusted for potential confounders. Results: Mean age was 24.6 years and 59.2% were nulliparous. Mean body mass index (BMI) was 20.1 kg/m2 and 22.9% were underweight. GDM was diagnosed in 36 women, corresponding to a prevalence of 12.3%. Of them, 8.2% were diagnosed before 24 weeks (early-onset) and 4.1% after 24 weeks (late-onset). Early-onset GDM contributed to 66.7% of GDM cases. GDM women had significantly higher age (p = 0.041) and BMI (p = 0.016) than those without GDM. Women who were > 25 - 29 years were significantly more likely to have GDM than those of ≤ 25 years (relative risk 1.91, 95% confidence interval 1.02-3.57, p = 0.041). The only independent associated factor associated with GDM was maternal age of > 25 - 29 years (adjusted odds ratio 2.21, 95% confidence interval 1.07-4.57, p = 0.032). Conclusion: Prevalence of GDM among women with lower risk was 12.3%. Independent associated factor was maternal age of > 25 - 29 years.